Assessment of Relationship between Intelligence Quotient and Orthodontic Treatment Need Procjena odnosa između kvocijenta inteligencije i potrebe za ortodontskom terapijom - YILMAZ, MÜESSER AHU; YILMAZ, HANİFE NURAY; AĞRALI, ÖMER BİRKAN; KARGÜL, BETÜL (My University, 2023)
Objective: Low cognitive ability may reduce the ability to understand the importance of oral health and to perform the necessary practices to maintain proper oral hygiene. Early loss of primary teeth following high caries risk may lead to malocclusion of permanent dentition. This study aimed to eval-uate the relationship between the cognitive levels of adolescents and their orthodontic treatment needs. Material and Methods: Between January 2018 and May 2018, 200 adolescents aged 10 – 15 who applied to the Pediatric Dentistry Clinic of Marmara University and sought orthodontic treatment were invited to participate in the study. The orthodontic treatment needs of 150 adolescents who agreed to participate were evaluated with the Index of Orthodontic Treatment Need-Aesthetic Component and their cognitive levels were evaluated with the Raven Standard Progressive Matrices (SPM) Test. P-value < 0.05 was considered statistically significant. Results: The mean age (± standard deviation) of 126 adolescents (77 females and 49 males) who completed the SPM test was 11.8 (± 1.3). There was no consistency between the intellectual level and the need for orthodontic treatment (Kappa value = 0.071, p-value = 0.081). There was no correlation between malocclusion sever-ity and intelligence quotient scores of adolescents (ρ [rho] =-0.089, p = 0.322). According to Mul-tiple logistic regression results, there was no difference between ‘borderline need’ (p = 0.059) and ‘great need’ (p = 0.881) from ‘no need’ for orthodontic treatment in adolescents with different intelligence quotients. Conclusions: The results showed no evidence for an association between maloc-clusion and intelligence quotient.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Adolescent; Child; Index of Orthodontic Treatment Need; Intelligence Test; Malocclusion; Persons with Mental Disabilities; Raven’s Progressive Matrices Test